HTML5 multimedia developer's guide - Bluttman, Ken; Cottrell, Lee (New Delhi Tata McGraw Hill, 2012)
"Develop cross-platform multimedia applications with HTML5. Now you can create rich, interactive content in the browser and deploy it across all platforms. HTML5 Multimedia Developer's Guide shows you how. You'll learn to use the revolutionary new features of HTML5, including the native audio, video, and drawing elements that eliminate the need for third-party plug-ins. New tags, the simplified doctype, local data storage, drag-and-drop, and geolocation are also covered. Detailed code examples illustrate the techniques discussed. By the end of the book, you'll be able to develop amazing multimedia applications and websites with HTML5. Use canvas for drawing, animation, effects, and events Create and view videos with the native video element Add and play audio files with the native audio element Take advantage of local data storage functions Apply drag-and-drop functionality Build location-aware web pages with the geolocation property Develop well-structured pages using the new semantic layout tags Add functionality to web forms with the new form objects Learn about new CSS3 properties and enhancements Use the editable content and offline files features Work with JavaScript and other technologies"--
"Now you can create rich, interactive content in the browser and deploy it across all platforms. HTML5 Multimedia Developer's Guide shows you how. You'll learn to use the revolutionary new features of HTML5, including the native audio, video, and drawing elements that eliminate the need for third-party plug-ins. New tags, the simplified doctype, local data storage, drag-and-drop, and geolocation are also covered. Detailed code examples illustrate the techniques discussed. By the end of the book, you'll be able to develop amazing multimedia applications and websites with HTML5"--
Includes index.
Keywords: HTML (Document markup language); Multimedia communications; Web site development